Study of the progressive collapse mechanism of excavations retained by cantilever contiguous piles. (January 2017) - Cheng, X.S.; Zheng, G.; Diao, Y.; Huang, T.M.; Deng, C.H.; Lei, Y.W.; Zhou, H.Z.
Abstract: An increasing number of catastrophic progressive collapses of deep excavations have occurred throughout the world. However, the mechanism by which partial failures evolve into large-scale progressive collapses has rarely been studied. In this paper, long-strip excavations and square excavations retained by cantilever contiguous piles under partial failure were simulated using the explicit finite difference method (FDM). The results show that a partial collapse can cause sharp increases in the internal forces in adjacent intact piles through the horizontal arching effect. Therefore, the concept of a load transfer coefficient is proposed, which is equal to the ratio of increase of the internal force in an intact pile. The relationship between the maximum load transfer coefficient T max and the safety factor of the piles determines whether progressive collapse will occur. Furthermore, the influences of a number of important factors on the load transfer mechanism, such as the capping beam, the extent of partial failure, the soil strength, the excavation depth and the corner effect, were examined. A continuous capping beam can reduce the maximum load transfer coefficient T max . Within a certain range of the extent of partial collapse, a larger partial collapse extent will produce larger load transfer coefficients and have a greater influence over a larger area. For the same retaining structure, a higher soil strength will result in larger load transfer coefficients. Moreover, when the lateral stiffness of the retaining piles is lower, the maximum load transfer coefficient will be smaller and the range of influence will be larger. In an excavation with a corner effect, when the number of failed piles is above a certain threshold, the maximum load transfer coefficient decreases with an increasing number of failed piles. Therefore, the progressive collapse evolving toward the corner will terminate when the maximum load transfer coefficient decreases below the safety factor. The corner effect can be recognized as a cause of the natural termination of progressive collapse. Highlights: Partial and progressive collapses of the excavations were simulated using FDM. Changing of the earth pressure and internal force after the collapse was examined. Load transfer coefficient was a determination factor of the progressive collapse. Corner effect was a cause of the natural termination of the progressive collapse.